Cellulose-based electronic carrier tape paper and preparation method thereof
By using a combination of cellulose-based materials, carbonyl modified basalt nanosheets and antistatic agents, high-performance cellulose-based electronic tape paper is prepared, which solves the production cost, environmental protection and antistatic of existing electronic tape papers. The shortcomings in performance and mechanical properties have achieved more efficient, safe and environmentally friendly packaging and transportation of electronic components.
Patent Information
- Application Number
- CN202411501324.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-02-18
AI Technical Summary
The existing electronic tape paper has obvious shortcomings in terms of high production costs, poor environmental protection performance, unstable anti-static performance and insufficient mechanical performance.
Using cellulose-based materials, cellulose nanofiber suspension is prepared by soaking and beating the wood pulp board, and mixing it with carbonyl-modified basalt nanosheets and antistatic agents to prepare high-performance cellulose-based cellulose through paper sample molding machine. Electronic carrier paper.
It significantly reduces the production cost of electronic tape paper, improves its environmental protection, anti-static performance and mechanical properties, and adapts to modern automated packaging processes.
Smart Images

Figure CN119465694A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electronic component packaging, and in particular to a cellulose-based electronic carrier paper and a preparation method thereof. Background Art
[0002] Electronic carrier paper is a material widely used in the packaging and transportation of electronic components. It is mainly used to fix and protect electronic components during production, storage and transportation. With the rapid development of the electronics industry, the demand for electronic carrier paper is increasing year by year. However, the existing electronic carrier paper technology has the following shortcomings: (1) High production cost. Currently, most electronic carrier papers on the market are made of synthetic materials such as polystyrene and polyester. Although these synthetic materials have certain strength and stability, their production cost is high, which is not conducive to reducing the overall cost of electronic products.
[0003] (2) Not environmentally friendly. Synthetic materials generate a large amount of environmental pollutants during production and processing, which are difficult to degrade and impose a serious burden on the ecological environment. With increasingly stringent environmental regulations and the improvement of people's environmental awareness, finding an environmentally friendly and low-cost electronic carrier paper material has become an urgent need in the industry.
[0004] (3) Static electricity. Static electricity is a hidden danger that cannot be ignored during the packaging and transportation of electronic components. The accumulation and release of static electricity may cause the performance of electronic components to deteriorate or even damage them, seriously affecting the quality and service life of the products. The anti-static performance of traditional electronic carrier paper is unstable, and it is often difficult to effectively suppress static electricity accumulation in the long term, increasing the risk of electronic components during transportation and storage. In order to ensure the safety and reliability of electronic components, it is particularly important to develop an electronic carrier paper with stable anti-static performance.
[0005] (4) Poor mechanical properties. The widespread application of automated packaging technology has put forward higher requirements on the mechanical properties of electronic carrier paper. Traditional electronic carrier paper is easily damaged due to insufficient mechanical strength during the automated packaging process, affecting packaging efficiency and product integrity. This lack of mechanical properties not only increases production costs, but may also cause damage to electronic components during transportation, resulting in economic losses. Therefore, improving the mechanical properties of electronic carrier paper so that it can adapt to modern automated packaging processes is an important direction for current technological improvements.
[0006] Therefore, the existing electronic carrier paper has obvious deficiencies in production cost, environmental protection performance, antistatic performance and mechanical performance. Summary of the invention
[0007] In view of the above-mentioned shortcomings of the prior art, the object of the present invention is to provide a cellulose-based electronic carrier paper and a preparation method thereof, so as to solve the problems of high production cost, poor environmental performance, antistatic performance and mechanical properties of the existing electronic carrier paper.
[0008] To achieve the above-mentioned object and other related objects, the present invention provides a method for preparing a cellulose-based electronic carrier paper, comprising: Step (1): soaking the first wood pulp board in water until the fibers swell, beating the pulp to obtain a pulp; in this step, the pulp is separated into fibers and brooms to obtain a pulp containing cellulose fibers; Step (2): reacting basalt nanosheets with polyvinyl pyrrolidone to obtain carbonyl-modified basalt nanosheets (CBSNs); Step (3): soaking the second wood pulp board in water until the pulp is completely disintegrated, and subjecting the pulp to pulping and microfluidization nano homogenization to obtain a cellulose nanofibril suspension (CNF); Step (4): uniformly mix the cellulose nanofibril suspension, carbonyl-modified basalt nanosheets and antistatic agent with the slurry obtained in step (1), form a paper sample to obtain a wet paper sheet, and dry it to obtain a cellulose-based electronic carrier paper.
[0009] Preferably, the diameter of the cellulose nanofibrils in the cellulose nanofibril suspension is 19.2-95.4 nm.
[0010] This application is based on the preparation of high-performance cellulose-based electronic carrier paper through a paper sheet former after mixing a slurry containing cellulose fibers, carbonyl-modified basalt nanosheets, cellulose nanofibrils CNF and an antistatic agent. It provides new ideas and methods for the rapid preparation of electronic carrier paper, making it significantly superior to traditional electronic carrier paper in terms of environmental protection, cost, electrostatic protection and mechanical properties. It provides a new, efficient, safe and environmentally friendly option for the packaging and transportation of electronic components, and enriches the current technical gap in the electronic carrier paper industry.
[0011] Preferably, the first wood pulp board and the second wood pulp board are both eucalyptus pulp boards.
[0012] Preferably, in step (1), the beating degree of the slurry is 35-45°SR, and the concentration of the slurry is 10wt%.
[0013] Preferably, in step (2), the mass ratio of the basalt nanosheets to polyvinyl pyrrolidone is 1:(2-20), and the reaction temperature is 25-60°C.
[0014] Preferably, in step (3), the refining is first performed by using a refiner and then by using an ultrafine grinding machine for grinding.
[0015] Preferably, the pulp concentration is 2-10 wt %, based on 15-30 g absolute dry weight, the speed of the refiner is 10000-30000 rpm; and the pulp obtained after refining is diluted to a concentration of 0.2-2.0 wt %.
[0016] Preferably, the grinding disc spacing of the ultrafine grinding machine is -10~100μm, the dosage is 5~20g, the rotation speed is 1000~2000r / min, and the processing time is 10~60min.
[0017] Preferably, the microfluidic nano-homogenization treatment uses a high-pressure microfluidic nano-homogenizer, the chamber of the high-pressure microfluidic nano-homogenizer is 87 μm and 200 μm, the homogenization pressure is 20-100 MPa, and the homogenization times are 1-20 times. The high-pressure microfluidic nano-homogenizer is used to mechanically peel off the cellulose to obtain cellulose nanofibrils (CNF).
[0018] Preferably, in step (4), the antistatic agent is selected from one or more of dimethyl distearyl ammonium chloride, dimethyl dimethoxyethyl ammonium chloride and trimethyl decyl ammonium chloride.
[0019] Preferably, in step (4), the amount of carbonyl-modified basalt nanosheets added to the slurry is 0.1-1.0 wt %, the amount of cellulose nanofibril suspension added is 2-20 wt %, and the amount of antistatic agent added is 1-10 wt %.
[0020] Preferably, in step (2), the method for preparing basalt nanosheets comprises the following steps: etching basalt flakes in an alkali solution, and then reacting them in a tetrabutylammonium solution to obtain expanded basalt flakes; dispersing the expanded basalt flakes in a mixed solution of hydrogen peroxide and an organic acid to react, washing them to neutrality, dispersing them in anhydrous ethanol, stirring and ultrasonically treating them to obtain basalt nanosheets.
[0021] In the above technical scheme of the present application, basalt scale (BS) is used as raw material, and preliminary surface etching is performed through alkali treatment to form a rough structure on its surface, and then treated with tetrabutylammonium. Due to the large radius of tetrabutylammonium ions and the high concentration of external tetrabutylammonium ions, the ion osmotic pressure is used to exchange with the metal ions inside the basalt scales, thereby occupying the inside of the basalt scales, generating certain cavities, and causing anisotropic expansion inside the basalt scales, destroying the internal interaction forces. The expanded basalt scales are placed in a mixed liquid system of hydrogen peroxide and organic acid. Hydrogen peroxide can enter the interlayer domain of the basalt scales by replacing with water molecules or forming dimers, and react with the hydrated cations in the interlayer domain with water molecules as the medium to produce Fenton reaction, decompose in situ to produce oxygen. And hydrogen peroxide can accelerate the decomposition rate under the catalytic action of organic acids to produce more oxygen. These gases will undergo violent cavitation between the basalt scales under mechanical stirring combined with ultrasonic action, causing the basalt scales to peel off again, forming a large number of basalt nanosheets (BSNs).
[0022] Preferably, the yield of the basalt nanosheets is 23.1-35.4 mg / h, and the diameter-to-thickness ratio is 513.2-982.3.
[0023] Preferably, the concentration of the tetrabutylammonium solution is 0.2~2moL / L, the mass volume ratio of the basalt flakes to the tetrabutylammonium solution is 1:(100~500)g / mL, the reaction time is 2~8h, the reaction temperature is 25~100°C, the stirring method is magnetic stirring or mechanical stirring, and the stirring rate is 500rpm~3000rpm.
[0024] Preferably, the mass volume ratio of the basalt flakes to the mixed solution of hydrogen peroxide and an organic acid is 1 g: (200-500) mL; the organic acid is one or both of maleic acid and oxalic acid.
[0025] Preferably, the mass fraction of the hydrogen peroxide is 10-30wt%.
[0026] Preferably, the mass volume ratio of the organic acid to hydrogen peroxide is (0.5-2):(200-500) g / mL.
[0027] The present invention also provides a cellulose-based electronic carrier paper prepared by the above preparation method.
[0028] Preferably, the cellulose-based electronic carrier paper has a tensile strength of 20.4-81.9 MPa and a surface resistivity of 1.2×10 6 ~9.8×10 8 Ω·cm, volume resistivity is 6.8×10 7 ~3.8×10 11Ω·cm, and the static decay time is 0.13~1.92s.
[0029] As described above, the present invention has the following beneficial effects: high-performance cellulose-based electronic carrier paper is prepared by mixing a slurry containing cellulose fibers, carbonyl-modified basalt nanosheets, cellulose nanofibrils CNF and an antistatic agent through a paper sheet former, which provides new ideas and methods for the rapid preparation of electronic carrier paper, making it significantly superior to traditional electronic carrier paper in terms of environmental protection, cost, electrostatic protection and mechanical properties, providing a new, efficient, safe and environmentally friendly option for the packaging and transportation of electronic components, and enriching the current technical gap in the electronic carrier paper industry. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 Shown are an atomic force microscope image (a) of the basalt nanosheets prepared in Example 1 and a thickness characterization image (b).
[0031] Figure 2 Optical photographs and Tyndall effect diagrams of cellulose nanofibril suspensions prepared with different homogenization times in Examples 1 to 5 (a to e) are shown. As the number of homogenization times increases, the Tyndall effect becomes increasingly obvious, indicating that the cellulose nanofibril suspension is relatively uniform.
[0032] Figure 3 The transmission electron microscopy images of cellulose nanofibrils prepared with different homogenization times in Examples 1 to 5 (a to e) are shown. As the homogenization times increase, the diameter of the cellulose nanofibrils gradually decreases and the aspect ratio gradually increases. DETAILED DESCRIPTION
[0033] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.
[0034] It should be noted that the process equipment or devices not specifically specified in the following embodiments are all conventional equipment or devices in the art.
[0035] In addition, it should be understood that one or more method steps mentioned in the present invention do not exclude the existence of other method steps before or after the combination step or the insertion of other method steps between these explicitly mentioned steps, unless otherwise specified; it should also be understood that the combination connection relationship between one or more devices / apparatuses mentioned in the present invention does not exclude the existence of other devices / apparatuses before or after the combination device / apparatus or the insertion of other devices / apparatuses between these explicitly mentioned two devices / apparatuses, unless otherwise specified. Moreover, unless otherwise specified, the numbering of each method step is only a convenient tool for identifying each method step, and is not intended to limit the order of arrangement of each method step or the scope of the present invention. Changes or adjustments in their relative relationships should also be regarded as the scope of the present invention without substantially changing the technical content.
[0036] Example 1 The present invention provides a method for preparing a cellulose-based electronic carrier paper, comprising the following steps: (1) Preparation of pulp: Take a certain mass of eucalyptus pulp board, tear it into pieces of about 5 cm × 5 cm, transfer it to deionized water and soak it for 12 h until the fibers swell, then mix it into a mass fraction of 10 wt% and use a Wall-E pulper to beat it to a beating degree of 35° SR to obtain a pulp with a concentration of 10 wt%. Wash and dehydrate the pulp in a pulp bag and balance the moisture for later use; (2) Preparation of carbonyl-modified basalt nanosheets: Untreated basalt flakes (BS) were placed in a 0.1 mol / L sodium hydroxide solution with a mass volume ratio of basalt flakes to sodium hydroxide solution of 1:150 g / mL. The surface etching reaction was carried out by stirring at a reaction temperature of 70°C for 6 h. The stirring method was magnetic stirring at a stirring rate of 1000 rpm. After the reaction was completed, the basalt flakes were filtered and washed to neutrality to obtain basalt flakes with preliminary surface etching. The basalt flakes with preliminary surface etching were then placed in a tetrabutylammonium solution with a concentration of 0.4 mol / L. The mass volume ratio of basalt flakes to tetrabutylammonium solution was 1:200 g / mL. The reaction was carried out by stirring at a temperature of 100°C with magnetic stirring at a stirring rate of 1000 rpm. After the reaction was completed, the basalt flakes were dried to obtain expanded basalt flakes. The expanded basalt flakes were dispersed in a mixed solution of hydrogen peroxide and an organic acid at a certain concentration, the mass volume ratio of the basalt flakes to the mixed solution was 1:300 g / mL, the mass fraction of hydrogen peroxide was 10wt%, the organic acid was maleic acid, and the mass volume ratio of maleic acid to hydrogen peroxide was 1:300 g / mL. The mixture was stirred and reacted at 40°C. After the reaction was completed, it was filtered and washed to neutrality, and then dispersed in anhydrous ethanol. The mixed solution was mechanically stirred and ultrasonically treated at a speed of 1000 rpm, an ultrasonic power of 700 W, and a reaction time of 25 min to obtain basalt nanosheets (BSNs). The prepared BSNs were stirred and reacted with a polyvinyl pyrrolidone solution at a mass ratio of 1g:5g and a stirring rate of 1000 rpm to obtain basalt nanosheets (CBSNs) containing carbonyl groups on the surface, namely carbonyl-modified basalt nanosheets. (3) Preparation of cellulose nanofibril suspension: The eucalyptus pulp board was soaked in deionized water until it was completely disintegrated, and then deionized water was added to dilute it to a pulp concentration of 2wt% and stirred evenly. It was then added to a PEI pulper with an addition amount of 15g (based on absolute dryness) and the pulping treatment was 10000rpm. The pulped pulp was then placed in an ultrafine grinder with a pulp concentration of 0.2wt% and an amount of 5g. The ultrafine grinder was ground at a grinding disc spacing of -10μm for 10min, and deionized water was added to the ground pulp to disperse it at a pulp concentration of 0.2wt%. The evenly dispersed pulp was treated by a high-pressure microfluidizer with chambers of 87μm and 200μm, a homogenization pressure of 20MPa, and a homogenization number of 1 to obtain a cellulose nanofibril (CNF) suspension. (4) Preparation of cellulose-based electronic carrier paper: Take a certain amount of pulp, add a certain mass of CBSNs, CNF and antistatic agent according to the set ratio, the pulp concentration is 10wt%, the mass is 2g, the CBSNs addition amount is 0.1wt%, the CNF addition amount is 2wt%, the antistatic agent is dimethyl distearyl ammonium chloride, and the antistatic agent addition amount is 1wt%. Place it in a pulp deagulator for stirring, the deagulator stirs at 5000rpm, and after stirring, it is formed into a wet paper sheet through a paper sample former, and then dried to obtain cellulose-based electronic carrier paper.
[0037] Figure 1 (a) is a transmission electron microscope image of the basalt nanosheets prepared in this embodiment. Figure 1 From (b) in the figure, it can be seen that the thickness of the basalt nanosheets prepared in this embodiment is 1.211 nm; Figure 2 (a) is an optical photograph and a Tyndall effect diagram of the cellulose nanofibril suspension prepared in this example. It can be seen from the figure that the Tyndall effect of the cellulose nanofibril suspension after one homogenization treatment is very weak; Figure 3 (a) is a transmission electron microscope image of the cellulose nanofibrils prepared in this example, from which it can be found that the diameter is relatively thick; from Table 1, it can be seen that the yield of basalt nanosheets is 23.1 mg / h, the diameter-to-thickness ratio is 513.2, the CNF diameter is 95.4 nm, the tensile strength is 20.4 MPa, and the surface resistivity of the prepared electronic carrier paper is 1.2×10 6 Ω·cm, volume resistivity is 6.8×10 7 Ω·cm, and the static decay time is 1.92s.
[0038] Example 2 The present invention provides a method for preparing a cellulose-based electronic carrier paper, comprising the following steps: (1) Preparation of pulp: Take a certain mass of eucalyptus pulp board, tear it into pieces of about 5 cm × 5 cm, transfer it to deionized water and soak it for 12 h until the fibers swell, then mix it into a mass fraction of 10 wt% and use a Wall-E pulper to beat it to a beating degree of 35° SR to obtain a pulp with a concentration of 10 wt%. Wash and dehydrate the pulp in a pulp bag and balance the moisture for later use; (2) Preparation of carbonyl-modified basalt nanosheets: Untreated basalt flakes (BS) were placed in a 0.3 mol / L sodium hydroxide solution, with a mass volume ratio of basalt flakes to sodium hydroxide solution of 1:200 g / mL. The surface was etched under stirring at a reaction temperature of 80°C for 8 hours. The stirring method was magnetic stirring at a stirring rate of 1500 rpm. After the reaction was completed, the basalt flakes were filtered and washed to neutrality to obtain basalt flakes with preliminary surface etching. Then, the basalt flakes with preliminary surface etching were placed in a tetrabutylammonium solution with a concentration of 0.5 mol / L. The mass volume ratio of basalt flakes to tetrabutylammonium solution was 1:200 g / mL. The reaction was stirred at a temperature of 40°C. The stirring method was mechanical stirring at a stirring rate of 1000 rpm. After the reaction was completed, the basalt flakes were dried to obtain expanded basalt flakes. The expanded basalt flakes were dispersed in a mixed solution of hydrogen peroxide and an organic acid at a certain concentration, the mass volume ratio of the basalt flakes to the mixed solution was 1g:200mL, the mass fraction of hydrogen peroxide was 15wt%, the organic acid was maleic acid, and the mass volume ratio of maleic acid to hydrogen peroxide was 1.0:200g / mL; the reaction was stirred at 30°C, and after the reaction was completed, the mixture was filtered and washed to neutrality, and then dispersed in anhydrous ethanol, and the mixed solution was mechanically stirred and ultrasonically treated, the mechanical stirring speed was 1000rpm, the ultrasonic power was 700W, and the reaction time was 40min to obtain basalt nanosheets (BSNs); the prepared BSNs were stirred and reacted with a polyvinyl pyrrolidone solution, the mass ratio of BSNs to polyvinyl pyrrolidone was 1:8, and the stirring rate was 1000rpm to obtain basalt nanosheets (CBSNs) containing carbonyl groups on the surface, namely carbonyl-modified basalt nanosheets; (3) Preparation of cellulose nanofibril suspension: Eucalyptus pulp was soaked in deionized water until it was completely disintegrated, then deionized water was added to dilute it to a pulp concentration of 4 wt% and stirred evenly, and then added to a PEI refiner with an addition amount of 15 g (based on absolute dryness) and a pulping treatment of 10,000 rpm; then the pulped pulp was placed in an ultrafine grinder with a pulp concentration of 0.4 wt% and an amount of 10 g, and ground at a grinding distance of -20 μm for 20 min, and deionized water was added to the ground pulp to disperse it with a pulp concentration of 0.4 wt%. The evenly dispersed pulp was treated by a high-pressure microfluidizer with chambers of 87 μm and 200 μm and a homogenization pressure of 40 MPa. After 5 homogenization times, a cellulose nanofibril (CNF) suspension was obtained; (4) Preparation of cellulose-based electronic carrier paper: Take a certain amount of pulp, add a certain mass of CBSNs, CNF and antistatic agent according to the set ratio, the pulp concentration is 10wt%, the mass is 2g, the CBSNs addition amount is 0.2wt%, the CNF addition amount is 4wt%, the antistatic agent is dimethyl dimethoxyethyl ammonium chloride, and the antistatic agent addition amount is 1wt%. Place it in a pulp deagulator for stirring, the deagulator stirs at 10000rpm, and after stirring, it is formed into a wet paper sheet through a paper sample former, and then dried to obtain cellulose-based electronic carrier paper.
[0039] Figure 2 (b) is an optical photograph and a Tyndall effect diagram of the cellulose nanofibril suspension prepared in this example. Figure 2 It can be seen that the cellulose nanofibrils obtained after 5 homogenization treatments are more evenly dispersed and have the Tyndall effect; Figure 3 (b) is a transmission electron microscope image of the cellulose nanofibrils prepared in this embodiment, which can be found to have a network structure. As shown in Table 1, the yield of the basalt nanosheets prepared in this embodiment is 27.5 mg / h, the aspect ratio is 612.5, the CNF diameter is 50.1 nm, the tensile strength is 40.1 MPa, and the surface resistivity of the electronic carrier paper prepared in this embodiment is 5.7×10 6 Ω·cm, volume resistivity is 8.7×10 7 Ω·cm, and the static decay time is 1.43s.
[0040] Example 3 The present invention provides a method for preparing a cellulose-based electronic carrier paper, comprising the following steps: (1) Preparation of pulp: Take a certain mass of eucalyptus pulp board, tear it into pieces of about 5 cm × 5 cm, transfer it to deionized water and soak it for 12 h until the fibers swell, then mix it into a mass fraction of 10 wt% and use a Wall-E pulper to beat it to a beating degree of 40° SR to obtain a pulp with a concentration of 10 wt%. Wash and dehydrate the pulp in a pulp bag and balance the moisture for later use; (2) Preparation of carbonyl-modified basalt nanosheets: Untreated basalt flakes (BS) were placed in a 0.5 mol / L sodium hydroxide solution, with a mass volume ratio of basalt flakes to sodium hydroxide solution of 1:200 g / mL. The surface was etched under stirring at a reaction temperature of 80°C for 12 h. The stirring method was mechanical stirring at a stirring rate of 1500 rpm. After the reaction was completed, the basalt flakes were filtered and washed to neutrality to obtain basalt flakes with preliminary surface etching. The basalt flakes with preliminary surface etching were then placed in a tetrabutylammonium solution with a concentration of 0.5 mol / L. The mass volume ratio of basalt flakes to tetrabutylammonium solution was 1:200 g / mL. The reaction was stirred at a temperature of 50°C. The stirring method was magnetic stirring at a stirring rate of 1500 rpm. After the reaction was completed, the basalt flakes were dried to obtain expanded basalt flakes. The expanded basalt flakes were dispersed in a mixed solution of hydrogen peroxide and an organic acid at a certain concentration, the mass volume ratio of the basalt flakes to the mixed solution was 1:300 g / mL, the mass fraction of hydrogen peroxide was 15wt%, the organic acid was oxalic acid, and the mass volume ratio of oxalic acid to hydrogen peroxide was 1.0:300 g / mL; the reaction was stirred at 40°C, and after the reaction was completed, the mixture was filtered and washed to neutrality, and then dispersed in anhydrous ethanol, and the mixed solution was mechanically stirred and ultrasonically treated, the mechanical stirring speed was 1500 rpm, the ultrasonic power was 700 W, and the reaction time was 40 min to obtain basalt nanosheets (BSNs); the prepared BSNs were stirred and reacted with a polyvinyl pyrrolidone solution, the mass ratio of BSNs to polyvinyl pyrrolidone was 1:10, and the stirring rate was 1000 rpm to obtain basalt nanosheets (CBSNs) containing carbonyl groups on the surface, that is, carbonyl-modified basalt nanosheets; (3) Preparation of cellulose nanofibril suspension: Eucalyptus pulp was soaked in deionized water until it was completely disintegrated, then deionized water was added to dilute it to a pulp concentration of 5wt% and stirred evenly, and then added to a PEI refiner with an addition amount of 20g (based on absolute dryness) and a pulping treatment of 10000rpm; then the pulped pulp was placed in an ultrafine grinder with a pulp concentration of 0.5wt% and an amount of 10g, and ground at a grinding disc spacing of -30μm for 30min, and deionized water was added to the ground pulp to disperse it with a pulp concentration of 0.5wt%. The evenly dispersed pulp was treated by a high-pressure microfluidizer with chambers of 87μm and 200μm and a homogenization pressure of 80MPa. After 10 times of homogenization, a cellulose nanofibril (CNF) suspension was obtained; (4) Preparation of cellulose-based electronic carrier paper: Take a certain amount of pulp, add a certain mass of CBSNs, CNF and antistatic agent according to the set ratio, the pulp concentration is 10wt%, the mass is 2g, the CBSNs addition amount is 0.5wt%, the CNF addition amount is 10wt%, the antistatic agent is trimethyldecyl ammonium chloride, the antistatic agent addition amount is 8wt%, place it in a pulp deagulator for stirring, the deagulator stirs at 10000rpm, after stirring is completed, it is formed into wet paper sheets through a paper sample former, and then dried to obtain cellulose-based electronic carrier paper.
[0041] Figure 2 (c) is an optical photograph and a Tyndall effect diagram of the cellulose nanofibril suspension prepared in this example. It can be seen from the figure that the Tyndall effect of the cellulose nanofibril suspension obtained after 10 homogenization treatments is further enhanced compared with 5 times, and the cellulose nanofibrils are more evenly dispersed; Figure 3 (c) is a transmission electron microscope image of the cellulose nanofibrils prepared in this embodiment, and it can be found that the diameter is reduced; as shown in Table 1, the yield of the basalt nanosheets prepared in this embodiment is 31.2 mg / h, the diameter-to-thickness ratio is 845.5, the CNF diameter is 34.5 nm, the tensile strength is 51.2 MPa, and the surface resistivity of the prepared electronic carrier paper is 3.1×10 7 Ω·cm, volume resistivity is 5.8×10 8 Ω·cm, and the static decay time is 0.82s.
[0042] Example 4 The present invention provides a method for preparing a cellulose-based electronic carrier paper, comprising the following steps: (1) Preparation of pulp: Take a certain mass of eucalyptus pulp board, tear it into pieces of about 5 cm × 5 cm, transfer it to deionized water and soak it for 12 h until the fibers swell, then mix it into a mass fraction of 10 wt% and use a Wall-E pulper to beat it to a beating degree of 40° SR to obtain a pulp with a concentration of 10 wt%. Wash and dehydrate the pulp in a pulp bag and balance the moisture for later use; (2) Preparation of carbonyl-modified basalt nanosheets: Untreated basalt flakes (BS) were placed in a 0.8 mol / L sodium hydroxide solution, with a mass volume ratio of basalt flakes to sodium hydroxide solution of 1:400 g / mL. The surface etching reaction was carried out by stirring at a reaction temperature of 100°C for 18 hours. The stirring method was mechanical stirring at a stirring rate of 2000 rpm. After the reaction was completed, the basalt flakes were filtered and washed to neutrality to obtain basalt flakes with preliminary surface etching; then the basalt flakes with preliminary surface etching were placed in a tetrabutylammonium solution with a concentration of 1.2 mol / L. The mass volume ratio of basalt flakes to tetrabutylammonium solution was 1:300 g / mL. The reaction was stirred at a temperature of 80°C. The stirring method was mechanical stirring at a stirring rate of 2000 rpm. After the reaction was completed, the basalt flakes were dried to obtain expanded basalt flakes. The expanded basalt flakes were dispersed in a mixed solution of hydrogen peroxide and an organic acid at a certain concentration, the mass volume ratio of the basalt flakes to the mixed solution was 1:400 g / mL, the mass fraction of hydrogen peroxide was 20wt%, the organic acid was oxalic acid, and the mass volume ratio of oxalic acid to hydrogen peroxide was 1.0:400 g / mL; the reaction was stirred at 40°C, and after the reaction was completed, the mixture was filtered and washed to neutrality, and then dispersed in anhydrous ethanol, and the mixed solution was mechanically stirred and ultrasonically treated, the mechanical stirring speed was 2000 rpm, the ultrasonic power was 800 W, and the reaction time was 50 min to obtain basalt nanosheets (BSNs); the prepared BSNs were stirred and reacted with a polyvinyl pyrrolidone solution, the mass ratio of BSNs to polyvinyl pyrrolidone was 1:15, and the stirring rate was 1000 rpm to obtain basalt nanosheets (CBSNs) containing carbonyl groups on the surface, that is, carbonyl-modified basalt nanosheets; (3) Preparation of cellulose nanofibril suspension: Eucalyptus pulp was soaked in deionized water until it was completely disintegrated, then deionized water was added to dilute it to a pulp concentration of 8 wt% and stirred evenly, and then added to a PEI pulper with an addition amount of 20 g (based on absolute dryness) and pulping at 20,000 rpm; then the pulped pulp was placed in an ultrafine grinder with a pulp concentration of 1.0 wt% and an amount of 15 g, and ground at a grinding distance of -80 μm for 50 min, and deionized water was added to the ground pulp to disperse it with a pulp concentration of 0.8 wt%. The evenly dispersed pulp was treated by a high-pressure microfluidizer with chambers of 87 μm and 200 μm and a homogenization pressure of 100 MPa. The homogenization times were 15 times, respectively, to obtain a cellulose nanofibril (CNF) suspension; (4) Preparation of cellulose-based electronic carrier paper: Take a certain amount of pulp, add a certain mass of CBSNs, CNF and antistatic agent according to the set ratio, the pulp concentration is 10wt%, the mass is 2g, the CBSNs addition amount is 0.8wt%, the CNF addition amount is 15wt%, the antistatic agent is trimethyldecyl ammonium chloride, the antistatic agent addition amount is 8wt%, place it in a pulp deagulator for stirring, the deagulator stirs at 15000rpm, after stirring is completed, it is formed into wet paper sheets through a paper sample former, and then dried to obtain cellulose-based electronic carrier paper.
[0043] Figure 2 (d) is an optical photograph and a Tyndall effect diagram of the cellulose nanofibril suspension prepared in this example. It can be seen from the figure that the Tyndall effect of the cellulose nanofibril suspension obtained after 15 homogenization treatments is further enhanced compared with 10 times, and the cellulose nanofibrils are more evenly dispersed; Figure 3 (d) is a transmission electron microscope image of the cellulose nanofibrils prepared in this embodiment, and it can be found that the diameter is reduced; as shown in Table 1, the yield of the basalt nanosheets prepared in this embodiment is 34.5 mg / h, the diameter-to-thickness ratio is 877.5, the CNF diameter is 27.1 nm, the tensile strength is 66.5 MPa, and the surface resistivity of the prepared electronic carrier paper is 2.8×10 8 Ω·cm, volume resistivity is 4.8×10 9 Ω·cm, and the static decay time is 0.57s.
[0044] Example 5 The present invention provides a method for preparing a cellulose-based electronic carrier paper, comprising the following steps: (1) Preparation of pulp: Take a certain mass of eucalyptus pulp board, tear it into pieces of about 5 cm × 5 cm, transfer it to deionized water and soak it for 12 h until the fibers swell, then mix it into a mass fraction of 10 wt% and use a Wall-E pulper to beat it to a beating degree of 45° SR. Wash and dehydrate the fully swollen pulp in a pulp bag and balance the moisture for later use; (2) Preparation of carbonyl-modified basalt nanosheets: Untreated basalt flakes (BS) were placed in a 1 mol / L sodium hydroxide solution, with a mass volume ratio of basalt flakes to sodium hydroxide solution of 1:500 g / mL. The surface was etched under stirring at a reaction temperature of 120°C for 24 h. The stirring method was magnetic stirring at a stirring rate of 3000 rpm. After the reaction was completed, the basalt flakes were filtered and washed to neutrality to obtain basalt flakes with preliminary surface etching. Then, the basalt flakes with preliminary surface etching were placed in a tetrabutylammonium solution with a concentration of 2 mol / L. The mass volume ratio of basalt flakes to tetrabutylammonium solution was 1:500 g / mL. The reaction was stirred at a temperature of 100°C. The stirring method was mechanical stirring at a stirring rate of 3000 rpm. After the reaction was completed, the basalt flakes were dried to obtain expanded basalt flakes. The expanded basalt flakes were dispersed in a mixed solution of hydrogen peroxide and an organic acid at a certain concentration, the mass volume ratio of the basalt flakes to the mixed solution was 1g:500mL, the mass fraction of hydrogen peroxide was 30wt%, the organic acid was oxalic acid, and the mass volume ratio of oxalic acid to hydrogen peroxide was 2.0:500g / mL; the reaction was stirred at 60°C, and after the reaction was completed, the mixture was filtered and washed to neutrality, and then dispersed in anhydrous ethanol, and the mixed solution was mechanically stirred and ultrasonically treated, the mechanical stirring speed was 2500rpm, the ultrasonic power was 1000W, and the reaction time was 60min to obtain basalt nanosheets (BSNs); the prepared BSNs were stirred and reacted with a polyvinyl pyrrolidone solution, the mass ratio of BSNs to polyvinyl pyrrolidone was 1:20, and the stirring rate was 1000rpm to obtain basalt nanosheets (CBSNs) containing carbonyl groups on the surface, that is, carbonyl-modified basalt nanosheets; (3) Preparation of cellulose nanofibril suspension: Eucalyptus pulp was soaked in deionized water until it was completely disintegrated, then deionized water was added to dilute it to a pulp concentration of 10 wt% and stirred evenly, and then added to a PEI pulper with an addition amount of 30 g (based on absolute dryness) and pulping at 30,000 rpm; then the pulped pulp was placed in an ultrafine grinder with a pulp concentration of 2.0 wt% and an amount of 20 g, and ground at a grinding distance of -100 μm for 60 min, and deionized water was added to the ground pulp to disperse it with a pulp concentration of 1.0 wt%. The evenly dispersed pulp was treated by a high-pressure microfluidizer with chambers of 87 μm and 200 μm, a homogenization pressure of 100 MPa, and 20 homogenization times to obtain a cellulose nanofibril (CNF) suspension; (4) Preparation of cellulose-based electronic carrier paper: Take a certain amount of pulp, add a certain mass of CBSNs, CNF and antistatic agent according to the set ratio, the pulp concentration is 10 wt%, the mass is 2 g, the CBSNs addition amount is 1.0 wt%, the CNF addition amount is 20 wt%, the antistatic agent is trimethyldecyl ammonium chloride, the antistatic agent addition amount is 10 wt%, place it in a pulp deagulator for stirring, the deagulator stirs at 20000 rpm, after stirring is completed, it is formed into wet paper sheets through a paper sample former, and then dried to obtain cellulose-based electronic carrier paper.
[0045] Figure 2 (e) is an optical photograph and a Tyndall effect diagram of the cellulose nanofibril suspension prepared in this example. It can be seen from the figure that the Tyndall effect of the cellulose nanofibril suspension obtained after 20 homogenization treatments is further enhanced compared with 15 times, and the cellulose nanofibrils are more evenly dispersed; Figure 3 (e) is a transmission electron microscope image of the cellulose nanofibrils prepared in this embodiment, and it can be found that the aspect ratio is relatively large; as shown in Table 1, the yield of the basalt nanosheets prepared in this embodiment is 35.4 mg / h, the diameter-to-thickness ratio is 982.3, the CNF diameter is 19.2 nm, the tensile strength is 81.9 MPa, and the surface resistivity of the prepared electronic carrier paper is 9.1×10 8 Ω·cm, volume resistivity is 3.8×10 11 Ω·cm, and the static decay time is 0.13s.
[0046] Table 1 shows the test results of the materials and cellulose-based electronic carrier paper prepared in Examples 1 to 5: Table 1. Test results of materials and cellulose-based electronic carrier paper prepared in Examples 1 to 5 The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. A method for preparing a cellulose-based electronic carrier paper, characterized in that: include: Step (1): soaking the first wood pulp board in water until the fibers swell, and beating the pulp to obtain a pulp; Step (2): reacting basalt nanosheets with polyvinyl pyrrolidone to obtain carbonyl-modified basalt nanosheets; Step (3): soaking the second wood pulp board in water until the pulp is completely disintegrated, and subjecting the pulp to pulping and microfluidization nano-homogenization treatment to obtain a cellulose nanofibril suspension; Step (4): uniformly mix the cellulose nanofibril suspension, carbonyl-modified basalt nanosheets and antistatic agent with the slurry obtained in step (1), form a paper sample to obtain a wet paper sheet, and dry it to obtain a cellulose-based electronic carrier paper.
2. The preparation method according to claim 1, characterized in that: In step (1), the beating degree of the slurry is 35-45°SR, and the concentration of the slurry is 10wt%.
3. The preparation method according to claim 1, characterized in that: In step (2), the mass ratio of the basalt nanosheets to polyvinyl pyrrolidone is 1:(2-20), and the reaction temperature is 25-60°C.
4. The preparation method according to claim 1, characterized in that: In step (3), the diameter of the cellulose nanofibril in the cellulose nanofibril suspension is 19.2-95.4 nm; the pulping is first performed by a pulping machine and then by a superfine grinding machine; the pulp concentration is 2-10 wt %, and the rotation speed of the pulping machine is 10000-30000 rpm based on 15-30 g absolute dry weight; the pulp obtained after the pulping is diluted to a concentration of 0.2-2.0 wt %, the grinding disc spacing of the superfine grinding machine is -10-100 μm, the dosage is 5-20 g, the rotation speed is 1000-2000 r / min, and the processing time is 10-60 min; the microfluidic nano homogenization treatment adopts a high-pressure microfluidic nano homogenizer, the chamber of the high-pressure microfluidic nano homogenizer is 87 μm and 200 μm, the homogenization pressure is 20-100 MPa, and the homogenization times are 1-20 times.
5. The preparation method according to claim 1, characterized in that: In step (4), the antistatic agent is selected from one or more of dimethyl distearyl ammonium chloride, dimethyl dimethoxyethyl ammonium chloride and trimethyl decyl ammonium chloride; the amount of carbonyl-modified basalt nanosheets added to the slurry is 0.1-1.0 wt%, the amount of the cellulose nanofibril suspension added is 2-20 wt%, and the amount of the antistatic agent added is 1-10 wt%.
6. The preparation method according to claim 1, characterized in that: In step (2), the method for preparing basalt nanosheets comprises the following steps: etching basalt flakes in an alkali solution, and then reacting them in a tetrabutylammonium solution to obtain expanded basalt flakes; dispersing the expanded basalt flakes in a mixed solution of hydrogen peroxide and an organic acid to react, washing them to neutrality, dispersing them in anhydrous ethanol, stirring and ultrasonically treating them to obtain basalt nanosheets.
7. The preparation method according to claim 6, characterized in that: The yield of the basalt nanosheets is 23.1~35.4mg / h, and the diameter-to-thickness ratio is 513.2~982.3; the concentration of the tetrabutylammonium solution is 0.2~2moL / L, the mass volume ratio of the basalt flakes to the tetrabutylammonium solution is 1g:(100~500)mL, the reaction time is 2~8h, the reaction temperature is 25~100℃, the stirring method is magnetic stirring or mechanical stirring, and the stirring rate is 500rpm~3000rpm.
8. The preparation method according to claim 7, characterized in that: The mass volume ratio of the basalt flakes to the mixed solution of hydrogen peroxide and organic acid is 1: (100~500) g / mL; the organic acid is one or two of maleic acid and oxalic acid; the mass fraction of hydrogen peroxide is 10~30wt%, and the mass volume ratio of the organic acid to hydrogen peroxide is (0.5~2): (200~500) g / mL.
9. A cellulose-based electronic carrier paper prepared by the preparation method according to any one of claims 1 to 9.
10. The cellulose-based electronic carrier paper according to claim 9, characterized in that: The tensile strength of the cellulose-based electronic carrier paper is 20.4-81.9 MPa, and the surface resistivity is 1.2×10 6 ~9.8×10 8 Ω⋅cm, volume resistivity is 6.8×10 7 ~3.8×10 11 Ω⋅cm, the static decay time is 0.13~1.92s.
Citation Information
Patent Citations
Preparation method of cellulose nanofiber filament
CN109295785A
Special paper for thin carrier tape and carrier tape
CN114277613A
High-performance basalt nanosheet-based paper insulating paint taking waste aramid fiber product as raw material and preparation method of high-performance basalt nanosheet-based paper insulating paint
CN118516876A
Carrier tape paper for electronic device
JP2000203521A
Mount for storing chip-type electronic component
JP2007238179A
Cited By
Preparation method of high-definition electronic screen protection paper
CN121295560A
A method for preparing a high-definition electronic screen protection paper
CN121295560B